The Influence of Climate Attitudes and Subjective and Social Norms on Supermarket Consumers' Intention Toward Climate-Friendly Food Consumption - Emberger-Klein, Agnes; Schöps, Johanna; Menrad, Klaus (Frontiers in Sustainable Food Systems, 2021)
Consumers can reduce greenhouse gas (GHG) emissions by changing their individual diets. Moreover, several studies showed that a positive intention to make climate-friendly food choices can be found among private consumers. Accordingly, the aim of this study was to analyze the factors, which influence supermarket consumers' behavioral intentions toward climate-friendly food consumption. For the analysis data from a face-to-face in-store survey in the southern Germany was used. The study was able to verify a large positive effect of Climate Attitudes and a medium positive effect of Subjective and social Norms on consumers' behavioral intention toward climate-friendly food consumption using an extended model of the Theory of Reasoned Action and structural equation modeling to analyze the data. However, the presumed direct effect of Perceived Behavioral Competency on this issue could not be proven. Based on the results strategies for the enhancement of climate-friendly food consumption are suggested.